(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Cholera is considered one of the common diseases in the world that affects the digestive system and is caused by Vibrio cholerae. This research was conducted in Al-Diwaniyah Governorate and its purpose is to investigate and count the number of infections for the years 2017-2018 and 2019-2020 .The number of confirmed cases for the year 2017 was 647, while for the year 2018 the numbers were 604 cases, for the year 2019 the number of cases was 364, and for the year 2020 the numbers were 436.Regarding age groups, the highest incidence of infection was (20 to 30) and the lowest incidence in age groups was (50 to 60) .Cases of diarrhea caused by infection with this type of Vibrio cholerae bacteria are transmitted to humans through eating food or drinking water contaminated with cholera bacteria. This disease is called the blue death as a result of lack of salts and loss of fluids to the body. Although cholera has been widespread throughout the world for some time, it is currently limited. In developing countries in tropical and subtropical regions, it is also common in epidemics